Influence of individual density and habitat availability on long-distance dispersal in a salt-marsh spider. Issue 1 (2nd January 2019) - Puzin, Charlène; Bonte, Dries; Pétillon, Julien
Abstract : Dispersal is a key process in metapopulation dynamics and metacommunity assembly as it may be affected by a variety of factors acting at different spatial scales. While dispersal is known to evolve in response to landscape-related selection pressures, local dynamics are merely driven by conditional responses, for instance by habitat quality and density. Local and regional factors are thus expected to impact dispersal, either synergistically or antagonistically. Moreover, such responses do not need to coincide among all life stages because different life stages are expected to incur different costs, either intrinsically due to for instance differences in size or extrinsically because of demographic changes. Our general objective is consequently to test for the likely opposite effects of main factors acting on dispersal, i.e. local density and habitat configuration, at different life-stages in a salt marsh inhabiting spider Pardosa purbeckensis (F.O.P.-Cambridge 1895). Using a combination of both field and laboratory experiments on pre-dispersal behaviour, we demonstrate a significant negative density-dependence for natal dispersal, but no alike effect at the adult stage. No effects of the local habitat structure were detected. Therefore, good mother body condition could be interpreted by juveniles during the phase of maternal care as suitable living conditions, decreasing emigration rate. Although dispersal is known to have a genetic basis, local factors eventually overrule this source of variation.